2010
DOI: 10.1097/tp.0b013e3181de5b8c
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Facing Renal Transplantation in Pediatric Patients With Lower Urinary Tract Dysfunction

Abstract: In pediatric patients with end-stage renal disease, renal transplantation is the established therapy of choice. The commonest cause is a congenital abnormality of the kidneys and urinary tract, often associated with lower urinary tract dysfunction (LUTD). Historically, such patients were denied transplantation, but it is now widely accepted that transplant outcomes comparable with the non-LUTD population are achievable. Nonetheless, the optimal management of pediatric end-stage renal disease patients with LUTD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 65 publications
(35 reference statements)
0
46
0
2
Order By: Relevance
“…Historically, there have been concerns over the suitability of RTx for patients with ESRD resulting from LUTD because of the expected higher risks of UTI and other urological [2,3]. Although some authors confirmed that outcomes for RTx in children with LUTD were similar to those in children with normal lower urinary tracts [9][10][11][12][13][14], LUTD may have a significant impact on graft survival if not managed appropriately [4,15]. Low intravesical pressure with adequate bladder capacity and compliance, together with efficient drainage, should be achieved for a successful transplantation [11,12,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, there have been concerns over the suitability of RTx for patients with ESRD resulting from LUTD because of the expected higher risks of UTI and other urological [2,3]. Although some authors confirmed that outcomes for RTx in children with LUTD were similar to those in children with normal lower urinary tracts [9][10][11][12][13][14], LUTD may have a significant impact on graft survival if not managed appropriately [4,15]. Low intravesical pressure with adequate bladder capacity and compliance, together with efficient drainage, should be achieved for a successful transplantation [11,12,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to reports by many other authors, we prefer reconstructive surgeries before RTx to avoid the possible adverse effects of immunosuppression, such as delayed wound healing and severe infection, in addition to the prevention of any harmful effect of LUTD on the graft [16,19]. It may not always be necessary to intervene in patients with borderline bladder compliance, however, as a small non-compliant bladder may improve after transplantation in some cases after restoration of urinary flow, sparing the patients a reconstructive surgery [10,21,22]. This requires close follow-up after transplantation to continuously assess the bladder and decide early on augmentation if needed.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Some pediatric kidney-transplant recipients require specialized ureteral reimplantation, bladder augmentation, or urinary diversion procedures. 35 …”
Section: Surgic a L Issues At Tr A Nspl A Ntationmentioning
confidence: 99%
“…In general terms, the actuarial global functional survival rate after the first year postoperatively was higher than 93%, and at year 5 it was between 75% and 85% ( Other authors have shown that patients with dysfunction in the urinary tract that required reconstructions had an increased risk of complications and loss of the graft (Mochon et al, 1992;Salomón et al, 1997). Such discrepancies can be explained because of the heterogeneity of the series published, the wide scope of the disease, the severity of the lower urinary tract and its different treatments (Riley et al, 2010) …”
Section: Graft Survivalmentioning
confidence: 71%
“…Nevertheless, there exists considerable controversy around the best approach to handle these types of patients, since there are no guidelines designed with defined reconstructive surgical criteria, optimal surgical procedures or recommendations as to when the best time to perform such interventions (Riley et al,2010).…”
Section: Introductionmentioning
confidence: 99%